Applied positive school psychology - Giraldez, Andrea; Burke, Jolanta (Abingdon, Oxon Routledge, Taylor & Francis Group, 2023)
"Applied Positive School Psychology is an essential guide to help teachers regain their own and assist the school community in rebuilding their health post-pandemic. While research in positive psychology is thriving, teachers and educational practitioners find it challenging to apply it in their daily practice. This practical book fills the gap between theory and practice and provides practitioners with an evidence-based toolkit on using the positive psychology in their school communities. With contributions from experts in their field, this important resource explores student wellbeing, teacher wellbeing, inclusion, developing positive relationships, creativity, and therapeutic art. Written with the practitioner in mind, Applied Positive School Psychology is a must read for the teaching community and those interested in positive education. It will also be of interest to academics specialising in wellbeing or education, educational psychologists, and education policy makers"--
Positive schools : an introduction -- Applying positive psychology in primary schools -- Positive relationships -- Self-confidence and self-efficacy development in schools -- Courage in positive education -- Working with strengths in education : why educators should strength spot in their students, and how students feel about this work -- Coaching conversations to enhance wellbeing -- Has life no meaning? Cultivating youth life meaning in schools -- Embedding compassion in schools : the what's, the why's and the how's -- Meditation-based tools for balance, focus and health -- Strength-based interventions for students or educators -- Arts and wellbeing -- Music, technology and wellbeing -- Playing and thriving in school -- Wellbeing lexicon in schools -- School belonging as an essential component of positive psychology in schools -- Positive psychology and school bullying -- Positive psychology, strengths-based and inclusive practices, and disability -- Positive solution -- The why and how of whole-school wellbeing -- Pedagogy for wellbeing : a new model for organic development of wellbeing in schools -- Wellbeing of school teachers -- Expertise : the problem with experience.
Includes bibliographical references and index.
Keywords: Positive psychology; School psychology; School children -- Psychology